ANALISIS KEPUASAN MASYARAKAT TERHADAP PELAYANAN UNIT REAKSI CEPAT (URC) DINAS PERHUBUNGAN KABUPATEN BOGOR - Wawan Hari Subagyo; Arry Muhammad Yusuf (Institut Teknologi dan Bisnis Dewantara, 2026)
This study evaluates service performance and community satisfaction with the URC services of the Bogor Regency Transportation Agency and identifies service indicators that require improvement. The research adopts a descriptive quantitative approach with 70 URC service users as respondents, and data were collected through questionnaires. Data analysis was conducted using the Service Quality (SQ), Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA) methods. The results show that although there is a negative gap between perceived performance and expectations, the overall service quality is considered good, with an average conformity level of 76.23%. The Customer Satisfaction Index (CSI) score of 65.68% indicates that customer satisfaction falls into the fairly satisfied category. IPA results reveal several important service indicators whose performance is still inadequate and therefore require priority improvements, including ease of understanding service requirements, compliance with procedures, assurance of traffic condition improvements after service actions, and the speed of complaint handling. The study concludes that although URC services have met expectations in many aspects, several critical aspects still need improvement to enhance overall service quality and customer satisfaction.